The Latino/a American Dream - White, John Kenneth, 1952-; Hanson, Sandra L.; White, John Kenneth, 1952- (Book collections on Project MUSE., 2016)
The "American Dream" means many things to many people, but in general it can be said that it connects the idea of freedom to the opportunity for prosperity and upward social mobility. Sandra L. Hanson and John K. White have joined together with a group of social scientists to explore the attitudes, experiences, and expectations of Latinos in their quest for the American Dream. The Latino/a American Dream asks many timely questions, including: how do Latino/as view the American Dream? Has the recent economic downturn affected their hopes of achieving the Dream? What about recent immigrants? Wha.